2011
DOI: 10.3390/catal2010056
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Evolution from Napiergrass by the Combination of Biological Treatment and a Pt-Loaded TiO2-Photocatalytic Reaction

Abstract: Ethanol and pentose were produced from lignocellulosic napiergrass by the simultaneous saccharification and fermentation process (SSF) using hydrolytic enzyme and S. Cerevisiae. After the ethanol was removed, the pentose solution was subjected to photocatalytic hydrogen evolution with Pt-loaded TiO 2 under UV-irradiation. This process converted 100 g of napiergrass into 12.3 g of ethanol and 1.76 g of hydrogen whose total combustion energy of (∆H) was 615 kJ. This was close to the ∆H (639 kJ) of the pentose (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…Extrapolating the produced H2 to infinite catalyst loading gives the limiting H2 yield (Nlim). 41,42 Conversion is calculated by dividing Nlim by the theoretical H2 yield, N100% (determined from Eq. 2, 4 and 6 for PLA, PET and PUR, respectively).…”
Section: Broader Contextmentioning
confidence: 99%
“…Extrapolating the produced H2 to infinite catalyst loading gives the limiting H2 yield (Nlim). 41,42 Conversion is calculated by dividing Nlim by the theoretical H2 yield, N100% (determined from Eq. 2, 4 and 6 for PLA, PET and PUR, respectively).…”
Section: Broader Contextmentioning
confidence: 99%
“…Moreover, it was confirmed that the H 2 evolution from water was small (2 mL) in the absence of xylose. Other gases such as CH 4 and CO were not observed in the evolved gas. …”
Section: Determination Of Limiting Mole Amount Of Hydrogen Evolved Frmentioning
confidence: 93%
“…Second generation bioethanol production from lignocellulosic biomass has been recognized as one of the promising approaches, since the lignocelluloses are not directly in competition with food sources [2]. Usual ethanol production from lignocellulose is conveniently achieved by simultaneous saccharification and fermentation (SSF) using Saccharomyces cerevisiae and hydrolytic enzymes [3,4]. However, the ethanol yield is low compared with the first generation bioethanol produced from starches which are composed of glucose units (Equation (1)), because of the high content of hemicellulose composed of xylose units, which are not utilized by S. cerevisiae.…”
Section: Introductionmentioning
confidence: 99%
“…The resulting water-soluble materials (saccharides, amino acids) are converted to biofuels such as ethanol, methane, and hydrogen through various catalytic reactions in aqueous solution. Our biomass reforming is performed in aqueous solution through sacrificial H 2 production over Pt/TiO 2 using water-soluble materials derived from lignocelluloses [19][20][21] and chlorella [22] (Figure 2).…”
Section: Outline Of Conversion Of Glycerol To Hydrogenmentioning
confidence: 99%